A Comparative Analysis Of Performance Of Power Supply Companies In The Duopoly Market Of Mumbai Region - THAKKAR, Dr. KINNARRY; PANDAGALE, PANKAJ DAYANAND (The journal of contemporary issues in business and government, 2021)
Power distribution system acts as a bridge between the customers and the utility. With changing times, the consumer’s expectation is not power supply to them but a reliable and quality power supply with timely redressal of complaints. With the advent of IT and mobile technologies changing our lives, consumers expect the utilities with accurate metering and billing free from any errors with facilities like online payment of bills and from mobile applications. Deregulated market operations are adopted by the major electric power utilities throughout the world because of the restricting process occurring rapidly. The only purpose to have stiff competition in the market of power sector is to increase the efficiency and productivity of the firms and at the same time to reduce the overall cost of the electricity and the simultaneous burden on the consumers. There is a constant need for generation, transmission and distribution of the electricity because this energy cannot be stored in large quantity or for a long period of time. Choosing between the parameters, continuous supply of electricity is given due preference over cost of the electrical energy. The deregulated structure has been adopted by the power firms in the nation just to meet the growing need of the power in the nation. There is a need for the formulation of the pool operating and system operating agencies to accommodate the integrated approach of the deregulation in the power sector of India. Alpha city i.e., Mumbai is the financial and commercial capital of India. Mumbai has three electricity distribution companies (discoms)–the state-run BEST Undertaking, and the private sector companies Adani Electricity and Tata Power Company. Tata Power is also a power generator supplying a bulk of the electricity that the city consumes. Tata Power offers multiple benefits to its consumers with the most competitive and economical tariff, along with delivering excellent customer service at par with international benchmarks. Mumbai is at a crossroads of threats to its cost and its service leadership, and it is time for utilities, consumer bodies, and regulators to come together and find solutions that will set an example in customer-centricity for the rest of the country to replicate. A good model will be one that enables improvement of efficiencies, reforms in tariffs, reduction of losses, and an improvement in reliability. And utilities will have to take the lead as they have a responsibility towards the citizens of Mumbai. It is time for all stakeholders to come together and plan with a long-term focus towards Mumbai's development and provide a platform to the rest of the country an example of excellence in customer centricity.